1995
DOI: 10.1159/000276741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Tranexamic Acid Gel in the Treatment of Epistaxis

Abstract: In patients with nosebleedings, the hemostatic effect of local application of tranexamic acid gel or placebo was compared in a randomized, double-blind, multicenter clinical trial with parallel groups. The times needed to arrest the initial bleeding were recorded, as well as any rebleedings within 10 days. The results showed no significant differences in any of the efficacy variables. Tranexamic acid was no better than placebo in the early treatment of nose bleedings, but the gel itself seemed to have a benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 4 publications
0
52
2
1
Order By: Relevance
“…In our study, nasal bleeding in ≈70% of patients in the tranexamic acid group was arrested within 10 minutes compared with ≈30% in the anterior nasal packing group, results similar to Petruson [12] using oral tranexamic acid. Unlike our results, Tibbelin et al [10], studying the effect of local tranexamic acid gel in the treatment of epistaxis in 68 patients, have reported that bleeding was arrested in 60% of patients compared with 76% in the placebo group within 30 minutes; however, it should be noted that we used injectable form of tranexamic acid with just a piece of cotton pledget. In the current study, only ≈3% of patients in the tranexamic acid group had rebleeding during 1 week compared with 11% in the anterior nasal packing group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, nasal bleeding in ≈70% of patients in the tranexamic acid group was arrested within 10 minutes compared with ≈30% in the anterior nasal packing group, results similar to Petruson [12] using oral tranexamic acid. Unlike our results, Tibbelin et al [10], studying the effect of local tranexamic acid gel in the treatment of epistaxis in 68 patients, have reported that bleeding was arrested in 60% of patients compared with 76% in the placebo group within 30 minutes; however, it should be noted that we used injectable form of tranexamic acid with just a piece of cotton pledget. In the current study, only ≈3% of patients in the tranexamic acid group had rebleeding during 1 week compared with 11% in the anterior nasal packing group.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, this technique may be used by a novice physician or a nurse. Tibbelin et al [10] showed the simplicity and convenience of use in application of an anterior nasal packing with tranexamic acid gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, provided that performance complied with principles, cauterization might be employed safely. Other treatments include; instillation of nasal saline spray [16], use of bland oils or ointments [10], topical nasal decongestant [20], intranasal sprays containing desmopressin, an anti-hemorrhagic agent [21], epsilon-aminocaproic acid [22], tranexamic acid gel [23] and fibrin sealant [24].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent years, it has been evaluated as an option for the management of uncomplicated epistaxis. 1,2 However, the role and efficacy of tranexamic acid in managing spontaneous epistaxis in patients receiving outpatient therapy with target-specific oral anticoagulants such as dabigatran, rivaroxaban, and apixaban is unclear. Here, we describe the first documented case of the use of topical tranexamic acid in an elderly patient with epistaxis complicated by outpatient therapy with rivaroxaban.…”
Section: Introductionmentioning
confidence: 99%